(untitled) (Global Business Management Review (GBMR), 2022)
The primary focus of the present study is to examine the influence of moral judgement, subjective norm and self-regulatory efficacy in predicting behavioural intention to purchase counterfeit products among Tanzanian consumers. This study also aims to examine the direct relationship between self-regulatory efficacy and purchase behaviour of counterfeit products. In addition, the present study also fills the gap in the intention-actual behaviour relationship by examining the moderating effect of idolatry on the relationship between consumers’ behavioural intention and purchase behaviour of counterfeit products. The present study also aims to examine to what extent intention to purchase counterfeit products contributes to the purchase behaviour of counterfeit products among Tanzanian consumers. It is an attempt to develop a conceptual framework for determining purchasing behaviour of counterfeit products in Tanzania. The aim is to provide adequate information to marketers on how to reap the expected benefits of sales as well as to facilitate prompt decision-making by the government through the execution and implementation of stringent regulations.